Exploring consumers’ attitude toward local TV commercials in the post-conflict marketing environment: Grounded theory approach - Shivany, S. (Sai Ram Institute of Business Management, 2011)
Consumers in the post conflict marketing environment are confronted with a large number of advertisement for many products and services. In such a cluttered media environment, one of the major challenges for advertising is to attract and retain the attention of consumers. Exploring consumer attitude of TV commercials provides knowledge to both academic and practitioners for modifying advertisement which are suited for the consumer preference. Using Grounded Theory approach, this study explores how marketing academics and the marketers can gain fresh insights into consumer attitude of TV commercials in the post-conflict marketing environment. Data were collected via 50 in-depth interviews undertaken in the four major cities of Northern Province of Sri Lanka. Study found that consumers in the post conflict environment have negative attitude towards local TV commercials. There is an attitude different among the local advertisement based on the features like advertising likability, social norms, interactivity, cultural aspects, emotional appeals, and the Celebrities. Irritation and repetition were found to be the important determinants of attitude towards local TV commercials. Additionally, there was evidence of influence from cultural resemblance that could motivate the people to enjoy the international TV commercials rather than local TV commercials. TV commercials which lead to greater enjoyment, allow consumers to learn more about brands and improve levels of comprehension. International advertisements, which subordinate interaction, were found to greatly increase the number of respondents liking. Further it was found that the advertisement associate with emotional appeals attract consumers more powerful than the advertisement which lack those appeals. Further, the study can provide practical suggestions on how to design effective commercial advertisement to fully utilize the advantages of the Television media. It is recommended that advertisers should think about entertainment for design advertisement. They should also decide apposite on what position they are aiming for, since that helps advertisement agencies to lay better positions on consumers mind, particularly consumers, who are returned to the normal life prefer enjoyable, cultural match, and fun associated advertisements rather than the long message content advertisement, and also they like the celebrities who appear their social patterns and ethnicity.
Keywords: Attitude; Grounded theory approach; Local TV commercials; Post - conflict Marketing Environment; Qualitative research